Amyotrophic lateral sclerosis: Origins traced to impaired balance between neural excitation and inhibition in the neonatal period. Issue 3 (5th July 2019) - Kiernan, Matthew C.; Ziemann, Ulf; Eisen, Andrew
ABSTRACT: Amyotrophic lateral sclerosis (ALS) is an adult onset disease but with an increasingly recognized preclinical prodrome. A wide spectrum of investigative approaches has identified loss of inhibitory function at the heart of ALS. In developing an explanation for the onset of ALS, it remains a consideration that ALS has its origins in neonatal derangement of the γ‐aminobutyric acid (GABA)‐ergic system, with delayed conversion from excitatory to mature inhibitory GABA and impaired excitation/inhibition balance. If this is so, the resulting chronic excitotoxicity could marginalize cortical network functioning very early in life, laying the path for neurodegeneration. The possibility that adult‐onset neurodegenerative conditions might have their roots in early developmental derangements is worthy of consideration, particularly in relation to current models of disease pathogenesis. Unraveling the very early molecular events will be crucial in developing a better understanding of ALS and other adult neurodegenerative disorders. Muscle Nerve, 2019